CARBON SEQUESTRATION OF MANGROVE ECOSYSTEM IN SEGARA ANAKAN LAGOON, INDONESIA - Endang Hilmi; Lilik Kartika Sari; Tri Nur Cahyo; Cecep Kusmana; Endang Suhendang (SEAMEO BIOTROP, 2019)
Carbon conservation programs in mangrove ecosystems focus on the growth of mangrove vegetation that is measured based on the amount of carbon present at different tree stages, particularly the seedlings, saplings, and mature mangrove trees. This study was aimed to determine carbon percentage of mangrove ecosystems using the SNI 06 — 3730 — 1995 and TAPPI T 211 om 85 methods, and to analyse the mangrove clustering based on carbon percentage. The results showed that (1) Avicennia spp., Sonneratia spp., Bruguiera spp., Rhizophora spp., Aegiceras spp., Lumnitzera spp., Ceriops spp., Excoecaria agallocha and Xylocarpus granatum had carbon percentages between 45.01% and 55.54%; (2) the carbon percentage of mangroves at different growth stages were as follows; seedlings at 16.3-21.2%, saplings at 19.0-28.1%, trees with diameter at breast height (DBH) of 10-20 cm at 38.1-46.30%, trees with DBH of 20-30 cm at 40.2-51.1% and trees with DBH of 30-40 cm at 49.1-55.20%. The carbon conservation is positively correlated with the carbon sequestration ability and growth of the mangroves.